Fireproof conductive silicone foam material and preparation method and application thereof

CN117050533BActive Publication Date: 2026-10-27SOUTH CHINA UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310953564.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2026-10-27
Estimated Expiration
2043-07-31

AI Technical Summary

Technical Problem

然而,有机硅泡沫的分子链连接有大量的有机侧基,在高温或暴露于火焰中时易发生断裂而燃烧,防火安全性不理想

Benefits of technology

[0030]本发明的原理:本发明以硅-氢加成反应和析氢反应为基础制备了具有高防火安全性的有机硅泡沫材料。分散在水中的纳米导电填料在水-油界面作用下可以随着气泡生长在泡孔内壁实现自组装,并与含氮硅烷修饰的碳纳米管协同作用从而提高有机硅泡沫材料的力学强度。而且,含氮硅烷修饰的碳纳米管在有机硅基体中分散均匀,并与界面组装的纳米导电填料协同构建导电网络(一维/二维协同导电网络)。同时,含氮硅烷修饰的碳纳米管还可以在高温下抑制铂的聚集,保持铂在高温下的催化活性,催化有机硅分子链的自由基交联反应,促进形成致密的陶瓷体交联网络,含氮硅烷修饰的碳纳米管与纳米导电填料起到骨架支撑作用,进一步完善陶瓷体,从而协同提高有机硅泡沫基体的阻燃性能和高温隔热性能。同时,含氮硅烷修饰的碳纳米管具有热电转换性能,可以使有机硅泡沫材料表现出灵敏的火灾预警性能,可以进一步提高其防火安全性。良好的弹性恢复能力和导电性使得有机硅泡沫材料可以用于压阻传感,实现对运动的实时监测,良好的导电性和泡孔界面组装可以赋予有机硅泡沫材料良好的电磁屏蔽性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117050533B_ABST
    Figure CN117050533B_ABST
Patent Text Reader

Abstract

The application discloses a fireproof conductive silicone foam material and a preparation method and application thereof. The composition components of the fireproof conductive silicone foam material include vinyl silicone oil, hydrogen-containing silicone oil, nano conductive filler, nitrogen-containing silane modified carbon nanotube, organic platinum compound and inhibitor. The preparation method of the fireproof conductive silicone foam material is very simple, that is, the components are mixed uniformly in batches, cross-linking-foaming is carried out at room temperature, cross-linking solidification is carried out after temperature rising, and the finished product is obtained. The fireproof conductive silicone foam material has the advantages of excellent flame-retardant performance, good conductive performance, excellent mechanical performance, light weight and the like, has sensitive fire early warning function, piezoresistance sensing function and electromagnetic shielding function and the like, and can be applied in the fields of aerospace, electronic communication, intelligent fire fighting, wearable equipment and the like on a large scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of organosilicon foam materials technology, specifically to a fire-resistant and conductive organosilicon foam material, its preparation method, and its application. Background Technology

[0002] Silicone foam materials possess advantages such as lightweight, resistance to high and low temperatures, aging resistance, good chemical stability, and good biocompatibility, making them widely used in automotive, aerospace, construction, electronic equipment, and biomedical fields. However, the molecular chains of silicone foams have numerous organic side groups, which are prone to breakage and combustion when exposed to high temperatures or flames, resulting in unsatisfactory fire safety. Currently, flame-retardant properties are mainly imparted to silicone foam materials by adding inorganic flame retardants, constructing flame-retardant coatings, and ceramicizing flame retardants. However, adding large amounts of flame retardants or ceramic fillers severely affects the processability of silicone foam materials, increases their density, and deteriorates their mechanical properties. Furthermore, flame-retardant coatings are susceptible to damage and have a short service life, significantly limiting the high-end applications of silicone foam materials.

[0003] Therefore, it is of great significance to develop an organosilicon foam material with excellent flame retardant properties, good electrical conductivity, excellent mechanical properties, and lightweight properties. Summary of the Invention

[0004] The purpose of this invention is to provide a fire-resistant and conductive silicone foam material, its preparation method, and its application.

[0005] The technical solution adopted in this invention is:

[0006] A fire-resistant and conductive silicone foam material, comprising the following components in parts by weight:

[0007] Vinyl silicone oil: 100 parts;

[0008] Hydrogen-containing silicone oil: 30 to 60 parts;

[0009] Nano-conductive filler: 0.3 parts to 10 parts;

[0010] Nitrogen-containing silane-modified carbon nanotubes: 0.5 parts to 15 parts;

[0011] Organoplasmic compounds: 0.2 to 1.5 parts;

[0012] Inhibitor: 0.02 to 0.5 parts.

[0013] Preferably, the viscosity of the vinyl silicone oil is 5000 mPa·s to 60000 mPa·s.

[0014] Preferably, the hydrogen content of the hydrogen-containing silicone oil is 0.5 wt% to 1.4 wt%.

[0015] Preferably, the nano-conductive filler is at least one of graphene oxide, aminated graphene oxide, carboxylated graphene oxide, titanium carbide, molybdenum carbide, and titanium nitride.

[0016] Preferably, the mass ratio of nitrogen-containing silane to carbon nanotubes in the nitrogen-containing silane-modified carbon nanotubes is 0.1 to 1.5:1.

[0017] Preferably, the nitrogen-containing silane in the nitrogen-containing silane-modified carbon nanotube is at least one of γ-aminopropyltrimethoxysilane, γ-piperazinylpropylmethyldimethoxysilane, and N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane.

[0018] Preferably, the carbon nanotubes in the nitrogen-containing silane-modified carbon nanotubes are at least one of carbon nanotubes, carboxylated carbon nanotubes, aminated carbon nanotubes, and hydroxylated carbon nanotubes.

[0019] Preferably, the length of the nitrogen-containing silane-modified carbon nanotube is 20 μm to 100 μm and the outer diameter is 10 nm to 20 nm.

[0020] Preferably, the organoplatinum compound is at least one of methylvinylsiloxane-platinum complex and vinylpolysiloxane-platinum complex.

[0021] Preferably, the platinum content of the organoplatinum compound is 1000ppm to 5000ppm.

[0022] Preferably, the inhibitor is at least one of 2-methyl-3-butyn-2-ol and 1-ethynyl-1-cyclohexanol.

[0023] A method for preparing a fire-retardant and conductive silicone foam material as described above includes the following steps:

[0024] 1) Mix vinyl silicone oil, ethanol dispersion of nitrogen-containing silane-modified carbon nanotubes and organoplatinum compound to prepare mixture A, and mix hydrogen-containing silicone oil, aqueous dispersion of nano-conductive filler and inhibitor to prepare mixture B.

[0025] 2) Mix mixture A and mixture B thoroughly and inject into a mold. Then, cross-link and foam at room temperature (25℃±5℃). After heating, cross-link and cure to obtain fireproof and conductive silicone foam material.

[0026] Preferably, the mass ratio of the nano-conductive filler to water in the aqueous dispersion of the nano-conductive filler in step 1) is 1:5 to 100.

[0027] Preferably, the cross-linking-foaming time in step 2) is 5 min to 30 min.

[0028] Preferably, the cross-linking curing in step 2) is carried out at a temperature of 50℃ to 80℃, and the cross-linking curing time is 0.5h to 3h.

[0029] A fire-retardant and conductive silicone foam material as described above is used for applications such as flame retardant insulation, fire early warning, piezoresistive sensing, or electromagnetic shielding.

[0030] The principle of this invention: This invention prepares an organosilicon foam material with high fire safety based on silicon-hydrogen addition reaction and hydrogen evolution reaction. Nano-conductive fillers dispersed in water can self-assemble on the inner wall of the bubble pores under the action of the water-oil interface, growing along with the bubbles, and synergistically interact with nitrogen-containing silane-modified carbon nanotubes to improve the mechanical strength of the organosilicon foam material. Furthermore, the nitrogen-containing silane-modified carbon nanotubes are uniformly dispersed in the organosilicon matrix and synergistically construct a conductive network (one-dimensional / two-dimensional synergistic conductive network) with the interface-assembled nano-conductive fillers. Simultaneously, the nitrogen-containing silane-modified carbon nanotubes can inhibit platinum aggregation at high temperatures, maintain the catalytic activity of platinum at high temperatures, catalyze the free radical cross-linking reaction of organosilicon molecular chains, and promote the formation of a dense ceramic cross-linking network. The nitrogen-containing silane-modified carbon nanotubes and nano-conductive fillers act as a skeletal support, further improving the ceramic body, thereby synergistically improving the flame retardant and high-temperature thermal insulation properties of the organosilicon foam matrix. At the same time, the nitrogen-containing silane-modified carbon nanotubes have thermoelectric conversion properties, enabling the organosilicon foam material to exhibit sensitive fire warning performance, further improving its fire safety. The excellent elastic recovery and conductivity of silicone foam materials enable them to be used in piezoresistive sensing for real-time motion monitoring. Their good conductivity and cell interface assembly also give them excellent electromagnetic shielding properties.

[0031] The fire-retardant conductive silicone foam material of this invention has the following applications: It can transform into a dense ceramic body under high-temperature burning, providing high-temperature insulation and protection for objects; based on its lightweight, shock-absorbing, and electromagnetic shielding properties, it can also be applied in electronics, communications, home appliances, military, aerospace, and other fields; by connecting the fire-retardant conductive silicone foam material to a digital multimeter and connecting it in series with a fire alarm, thresholds can be preset according to different needs. When exposed to a certain temperature, due to the thermoelectric effect, the internal charge carriers move along the temperature gradient, generating a thermoelectric voltage, triggering the alarm device, and realizing the fire alarm function; connecting the fire-retardant conductive silicone foam material to a digital multimeter can realize piezoresistive sensing detection of different human body movements, making it suitable for application in the field of wearable devices.

[0032] The beneficial effects of the present invention are: the fireproof and conductive silicone foam material of the present invention has the advantages of excellent flame retardant properties, good conductivity, excellent mechanical properties, and lightweight, and has multiple functions such as sensitive fire early warning function, piezoresistive sensing function and electromagnetic shielding function, and can be widely used in aerospace, electronic communication, intelligent fire protection, wearable devices and other fields.

[0033] Specifically:

[0034] 1) The fireproof and conductive silicone foam material of the present invention contains nitrogen-containing silane-modified carbon nanotubes. By modifying the carbon nanotubes with nitrogen-containing silane, on the one hand, the dispersion of carbon nanotubes in the silicone matrix can be improved, and on the other hand, the nitrogen-containing silane can coordinate with platinum, thereby inhibiting the aggregation of platinum atoms under high temperature. This is beneficial to the efficient catalysis of free radical cross-linking reaction of silicone matrix by platinum atoms at high temperature. It also works synergistically with nano-conductive fillers to form a more solid and dense ceramic barrier layer, which can block heat and oxygen, giving the silicone foam material excellent flame retardant and high temperature insulation properties, and avoiding the damage to the performance of silicone foam material caused by adding a large amount of ceramic filler.

[0035] 2) This invention enables the self-assembly of nano-conductive fillers on the inner wall of the foam cells through the interaction of the water-oil interface, and synergistically improves the mechanical and electrical properties of the foam material with carbon nanotubes, while endowing it with multiple functions. In particular, based on the thermoelectric effect of carbon nanotubes, the organosilicon foam material also has a sensitive fire early warning function, which further improves its fire safety and expands its application scenarios.

[0036] 3) The fireproof and conductive silicone foam material of the present invention can be foamed and cured within minutes at room temperature. The process is simple, green and environmentally friendly. The silicone foam material prepared in the end has uniform cells, is flexible and elastic, and has excellent mechanical properties, making it suitable for large-scale promotion and application. Attached Figure Description

[0037] Figure 1 This is a diagram illustrating the cell growth process of the fire-retardant and conductive silicone foam material in Example 1.

[0038] Figure 2 The image shows a cross-sectional SEM image and elemental distribution diagram of the fire-resistant and conductive silicone foam material of Example 1.

[0039] Figure 3 The figure shows the mechanical property test results of the fireproof and conductive silicone foam material in Example 1.

[0040] Figure 4 This is a photograph of the silicone foam material from Comparative Example 1 after a high-temperature insulation test.

[0041] Figure 5This is a photograph of the fire-resistant and conductive silicone foam material from Example 1 after a high-temperature insulation test.

[0042] Figure 6 The XRD pattern of the ceramic-like body formed after high-temperature thermal insulation testing of the fireproof and conductive silicone foam material of Example 1.

[0043] Figure 7 The image shown is a screenshot from a fire warning test video of the fire-resistant and conductive silicone foam material used in Example 1.

[0044] Figure 8 The graph shows the results of repeated piezoresistive sensing tests on the fire-resistant conductive silicone foam material of Example 1. Detailed Implementation

[0045] The present invention will be further explained and described below with reference to specific embodiments.

[0046] Example 1:

[0047] A fire-resistant and conductive silicone foam material, the preparation method of which includes the following steps:

[0048] 1) Disperse 2 parts by mass of carbon nanotubes (length 20μm~100μm, outer diameter 10nm~20nm) with 60 parts by mass of ethanol, then add 1.4 parts by mass of γ-aminopropyltrimethoxysilane and stir at room temperature for 24h to obtain an ethanol dispersion of nitrogen-containing silane-modified carbon nanotubes.

[0049] 2) Mix 100 parts by mass of vinyl silicone oil with a viscosity of 10000 mPa·s and ethanol dispersion of nitrogen-containing silane-modified carbon nanotubes, stir until the ethanol is completely evaporated, add 0.7 parts by mass of methyl vinylsiloxane-platinum complex (platinum content of 3000 ppm), and then mechanically stir at a stirring rate of 800 rpm for 5 min to obtain mixture A;

[0050] 3) Mix 50 parts by mass of hydrogen-containing silicone oil with a hydrogen content of 0.7 wt%, 50 parts by mass of titanium carbide aqueous dispersion (titanium carbide and water in a mass ratio of 1:20), and 0.05 parts by mass of 2-methyl-3-butyn-2-ol, and then mechanically stir at a stirring speed of 800 rpm for 5 min to obtain mixture B.

[0051] 4) Mix mixture A and mixture B, then mechanically stir at a stirring rate of 500 rpm for 50 seconds, then pour into a mold, and then crosslink and foam at room temperature for 10 minutes. After heating to 50℃, crosslink and cure for 1 hour to obtain fireproof and conductive silicone foam material.

[0052] Example 2:

[0053] A fire-resistant and conductive silicone foam material, the preparation method of which includes the following steps:

[0054] 1) Disperse 0.5 parts by mass of carbon nanotubes (length 20μm~100μm, outer diameter 10nm~20nm) with 15 parts by mass of ethanol, then add 0.05 parts by mass of γ-aminopropyltrimethoxysilane and stir at room temperature for 12h to obtain an ethanol dispersion of nitrogen-containing silane-modified carbon nanotubes.

[0055] 2) Mix 100 parts by mass of vinyl silicone oil with a viscosity of 10000 mPa·s and ethanol dispersion of nitrogen-containing silane-modified carbon nanotubes, stir until the ethanol is completely evaporated, add 0.2 parts by mass of methyl vinylsiloxane-platinum complex (platinum content of 1000 ppm), and then mechanically stir at a stirring rate of 500 rpm for 5 min to obtain mixture A;

[0056] 3) Mix 30 parts by mass of hydrogen-containing silicone oil with a hydrogen content of 0.5 wt%, 30 parts by mass of titanium carbide aqueous dispersion (titanium carbide and water in a mass ratio of 1:5), and 0.02 parts by mass of 2-methyl-3-butyn-2-ol, and then mechanically stir at a stirring speed of 800 rpm for 5 min to obtain mixture B.

[0057] 4) Mix mixture A and mixture B, then mechanically stir at a stirring rate of 500 rpm for 50 s, then pour into a mold, and then crosslink and foam at room temperature for 5 min, and then heat to 50℃ for 0.5 h for crosslinking and curing to obtain fireproof and conductive silicone foam material.

[0058] Example 3:

[0059] A fire-resistant and conductive silicone foam material, the preparation method of which includes the following steps:

[0060] 1) Disperse 6 parts by mass of carbon nanotubes (length 20μm~100μm, outer diameter 10nm~20nm) with 180 parts by mass of ethanol, then add 9 parts by mass of γ-aminopropyltrimethoxysilane and stir at room temperature for 48h to obtain an ethanol dispersion of nitrogen-containing silane-modified carbon nanotubes.

[0061] 2) Mix 100 parts by mass of vinyl silicone oil with a viscosity of 60000 mPa·s and ethanol dispersion of nitrogen-containing silane-modified carbon nanotubes, and stir until the ethanol is completely evaporated. Then add 1.5 parts by mass of methyl vinylsiloxane-platinum complex (platinum content of 5000 ppm), and mechanically stir at a stirring rate of 1000 rpm for 10 min to obtain mixture A.

[0062] 3) Mix 60 parts by mass of hydrogen-containing silicone oil with a hydrogen content of 1.4 wt%, 60 parts by mass of titanium carbide aqueous dispersion (titanium carbide and water in a mass ratio of 1:100), and 0.5 parts by mass of 2-methyl-3-butyn-2-ol, and then mechanically stir at a stirring rate of 800 rpm for 10 min to obtain mixture B.

[0063] 4) Mix mixture A and mixture B, then mechanically stir at a stirring rate of 1000 rpm for 50 seconds, then pour into a mold, and then crosslink and foam at room temperature for 30 minutes. After heating to 80℃, crosslink and cure for 3 hours to obtain fireproof and conductive silicone foam material.

[0064] Example 4:

[0065] A fire-resistant and conductive silicone foam material, the preparation method of which includes the following steps:

[0066] 1) Disperse 2 parts by mass of carboxylated carbon nanotubes (length 20 μm to 100 μm, outer diameter 10 nm to 20 nm) with 60 parts by mass of ethanol, then add 1.4 parts by mass of γ-piperazinylpropylmethyldimethoxysilane and stir at room temperature for 24 h to obtain an ethanol dispersion of nitrogen-containing silane-modified carbon nanotubes.

[0067] 2) Mix 100 parts by mass of vinyl silicone oil with a viscosity of 10000 mPa·s and ethanol dispersion of nitrogen-containing silane-modified carbon nanotubes, stir until the ethanol is completely evaporated, add 0.4 parts by mass of vinyl polysiloxane-platinum complex (platinum content of 3000 ppm), and then mechanically stir at a stirring rate of 800 rpm for 5 min to obtain mixture A;

[0068] 3) Mix 50 parts by mass of hydrogen-containing silicone oil with a hydrogen content of 0.7 wt%, 50 parts by mass of an aqueous dispersion of graphene oxide (the mass ratio of graphene oxide to water is 1:20), and 0.05 parts by mass of 2-methyl-3-butyn-2-ol, and then mechanically stir at a stirring speed of 800 rpm for 5 min to obtain mixture B.

[0069] 4) Mix mixture A and mixture B, then mechanically stir at a stirring rate of 500 rpm for 50 seconds, then pour into a mold, and then crosslink and foam at room temperature for 10 minutes. After heating to 50℃, crosslink and cure for 1 hour to obtain fireproof and conductive silicone foam material.

[0070] Example 5:

[0071] A fire-resistant and conductive silicone foam material, the preparation method of which includes the following steps:

[0072] 1) Disperse 2 parts by mass of aminated carbon nanotubes (length 20 μm to 100 μm, outer diameter 10 nm to 20 nm) with 60 parts by mass of ethanol, then add 1.4 parts by mass of γ-piperazinylpropylmethyldimethoxysilane and stir at room temperature for 24 h to obtain an ethanol dispersion of nitrogen-containing silane-modified carbon nanotubes.

[0073] 2) Mix 100 parts by mass of vinyl silicone oil with a viscosity of 10000 mPa·s and ethanol dispersion of nitrogen-containing silane-modified carbon nanotubes, stir until the ethanol is completely evaporated, add 0.9 parts by mass of vinyl polysiloxane-platinum complex (platinum content of 3000 ppm), and then mechanically stir at a stirring rate of 800 rpm for 5 min to obtain mixture A;

[0074] 3) Mix 50 parts by mass of hydrogen-containing silicone oil with a hydrogen content of 0.7 wt%, 50 parts by mass of an aqueous dispersion of carboxylated graphene oxide (the mass ratio of carboxylated graphene oxide to water is 1:20), and 0.05 parts by mass of 2-methyl-3-butyn-2-ol, and then mechanically stir at a stirring speed of 800 rpm for 5 min to obtain mixture B;

[0075] 4) Mix mixture A and mixture B, then mechanically stir at a stirring rate of 500 rpm for 50 seconds, then pour into a mold, and then crosslink and foam at room temperature for 10 minutes. After heating to 50℃, crosslink and cure for 1 hour to obtain fireproof and conductive silicone foam material.

[0076] Example 6:

[0077] A fire-resistant and conductive silicone foam material, the preparation method of which includes the following steps:

[0078] 1) Disperse 2 parts by mass of aminated carbon nanotubes (length 20 μm to 100 μm, outer diameter 10 nm to 20 nm) with 60 parts by mass of ethanol, then add 1.4 parts by mass of N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane and stir at room temperature for 24 h to obtain an ethanol dispersion of nitrogen-containing silane-modified carbon nanotubes.

[0079] 2) Mix 100 parts by mass of vinyl silicone oil with a viscosity of 10000 mPa·s and ethanol dispersion of nitrogen-containing silane-modified carbon nanotubes, stir until the ethanol is completely evaporated, then add 1.2 parts by mass of vinyl polysiloxane-platinum complex (platinum content of 3000 ppm), and then mechanically stir at a stirring rate of 800 rpm for 5 min to obtain mixture A;

[0080] 3) Mix 50 parts by mass of hydrogen-containing silicone oil with a hydrogen content of 0.7 wt%, 50 parts by mass of molybdenum carbide aqueous dispersion (molybdenum carbide and water in a mass ratio of 1:20), and 0.05 parts by mass of 1-ethynyl-1-cyclohexanol, and then mechanically stir at a stirring speed of 800 rpm for 5 min to obtain mixture B.

[0081] 4) Mix mixture A and mixture B, then mechanically stir at a stirring rate of 500 rpm for 50 seconds, then pour into a mold, and then crosslink and foam at room temperature for 10 minutes. After heating to 50℃, crosslink and cure for 1 hour to obtain fireproof and conductive silicone foam material.

[0082] Example 7:

[0083] A fire-resistant and conductive silicone foam material, the preparation method of which includes the following steps:

[0084] 1) Disperse 2 parts by mass of hydroxylated carbon nanotubes (length 20 μm to 100 μm, outer diameter 10 nm to 20 nm) with 60 parts by mass of ethanol, then add 1.4 parts by mass of N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane and stir at room temperature for 24 h to obtain an ethanol dispersion of nitrogen-containing silane-modified carbon nanotubes.

[0085] 2) Mix 100 parts by mass of vinyl silicone oil with a viscosity of 10000 mPa·s and ethanol dispersion of nitrogen-containing silane-modified carbon nanotubes, stir until the ethanol is completely evaporated, add 1.4 parts by mass of methyl vinylsiloxane-platinum complex (platinum content of 3000 ppm), and then mechanically stir at a stirring rate of 800 rpm for 5 min to obtain mixture A;

[0086] 3) Mix 50 parts by mass of hydrogen-containing silicone oil with a hydrogen content of 0.7 wt%, 50 parts by mass of an aqueous dispersion of carboxylated graphene oxide (the mass ratio of carboxylated graphene oxide to water is 1:20), and 0.05 parts by mass of 1-ethynyl-1-cyclohexanol, and then mechanically stir at a stirring speed of 800 rpm for 5 min to obtain mixture B;

[0087] 4) Mix mixture A and mixture B, then mechanically stir at a stirring rate of 500 rpm for 50 seconds, then pour into a mold, and then crosslink and foam at room temperature for 10 minutes. After heating to 50℃, crosslink and cure for 1 hour to obtain fireproof and conductive silicone foam material.

[0088] Example 8:

[0089] A fire-resistant and conductive silicone foam material, the preparation method of which includes the following steps:

[0090] 1) Disperse 2 parts by mass of hydroxylated carbon nanotubes (length 20 μm to 100 μm, outer diameter 10 nm to 20 nm) with 60 parts by mass of ethanol, then add 1.4 parts by mass of γ-aminopropyltrimethoxysilane and stir at room temperature for 24 h to obtain an ethanol dispersion of nitrogen-containing silane-modified carbon nanotubes.

[0091] 2) Mix 100 parts by mass of vinyl silicone oil with a viscosity of 10000 mPa·s and ethanol dispersion of nitrogen-containing silane-modified carbon nanotubes, stir until the ethanol is completely evaporated, add 0.7 parts by mass of vinyl polysiloxane-platinum complex (platinum content of 3000 ppm), and then mechanically stir at a stirring rate of 800 rpm for 5 min to obtain mixture A;

[0092] 3) Mix 50 parts by mass of hydrogen-containing silicone oil with a hydrogen content of 0.7 wt%, 50 parts by mass of aqueous dispersion of titanium nitride (the mass ratio of titanium nitride to water is 1:20), and 0.05 parts by mass of 2-methyl-3-butyn-2-ol, and then mechanically stir at a stirring speed of 800 rpm for 5 min to obtain mixture B.

[0093] 4) Mix mixture A and mixture B, then mechanically stir at a stirring rate of 500 rpm for 50 seconds, then pour into a mold, and then crosslink and foam at room temperature for 10 minutes. After heating to 50℃, crosslink and cure for 1 hour to obtain fireproof and conductive silicone foam material.

[0094] Comparative Example 1:

[0095] An organosilicon foam material, the preparation method of which includes the following steps:

[0096] 1) Mix 100 parts by mass of vinyl silicone oil with a viscosity of 10000 mPa·s and 0.7 parts by mass of methyl vinyl siloxane-platinum complex (platinum content of 3000 ppm), and then mechanically stir at a stirring speed of 800 rpm for 5 min to obtain mixture A;

[0097] 2) Mix 50 parts by mass of hydrogen-containing silicone oil with a hydrogen content of 0.7 wt%, 50 parts by mass of water and 0.05 parts by mass of 1-ethynyl-1-cyclohexanol, and then mechanically stir at a stirring speed of 800 rpm for 5 min to obtain mixture B.

[0098] 3) Mix mixture A and mixture B, then mechanically stir at a stirring rate of 500 rpm for 50 seconds, then pour into a mold, and then perform cross-linking-foaming at room temperature for 10 minutes. After that, heat to 50℃ and perform cross-linking curing for 1 hour to obtain the silicone foam material.

[0099] Comparative Example 2:

[0100] An organosilicon foam material, the preparation method of which includes the following steps:

[0101] 1) Mix 100 parts by mass of vinyl silicone oil with a viscosity of 10000 mPa·s, 0.7 parts by mass of methyl vinyl siloxane-platinum complex (platinum content of 3000 ppm) and 0.7 parts by mass of γ-aminopropyltrimethoxysilane, and then mechanically stir at a stirring rate of 800 rpm for 5 min to obtain mixture A.

[0102] 2) Mix 50 parts by mass of hydrogen-containing silicone oil with a hydrogen content of 0.7 wt%, 50 parts by mass of water and 0.05 parts by mass of 1-ethynyl-1-cyclohexanol, and then mechanically stir at a stirring speed of 800 rpm for 5 min to obtain mixture B.

[0103] 3) Mix mixture A and mixture B, then mechanically stir at a stirring rate of 500 rpm for 50 seconds, then pour into a mold, and then perform cross-linking-foaming at room temperature for 10 minutes. After that, heat to 50℃ and perform cross-linking curing for 1 hour to obtain the silicone foam material.

[0104] Comparative Example 3:

[0105] An organosilicon foam material, the preparation method of which includes the following steps:

[0106] 1) Mix 100 parts by mass of vinyl silicone oil with a viscosity of 10000 mPa·s, 0.7 parts by mass of methyl vinyl siloxane-platinum complex (platinum content of 3000 ppm) and 0.7 parts by mass of γ-aminopropyltrimethoxysilane, and then mechanically stir at a stirring rate of 800 rpm for 5 min to obtain mixture A.

[0107] 2) Mix 50 parts by mass of hydrogen-containing silicone oil with a hydrogen content of 0.7 wt%, 50 parts by mass of titanium carbide aqueous dispersion (titanium carbide and water in a mass ratio of 1:20), and 0.05 parts by mass of 1-ethynyl-1-cyclohexanol, and then mechanically stir at a stirring speed of 800 rpm for 5 min to obtain mixture B.

[0108] 3) Mix mixture A and mixture B, then mechanically stir at a stirring rate of 500 rpm for 50 seconds, then pour into a mold, and then perform cross-linking-foaming at room temperature for 10 minutes. After that, heat to 50℃ and perform cross-linking curing for 1 hour to obtain the silicone foam material.

[0109] Performance testing:

[0110] Test method:

[0111] Foaming process: Mixture A and mixture B are mixed on a glass slide, and the foaming process is observed under a polarizing microscope (Carl Zeiss GmbH, Germany, model: Axiocam 208color).

[0112] Scanning electron microscopy (SEM) test: The sample was adhered to the sample stage with conductive adhesive and then surface-sprayed with gold. The surface morphology of the sample was then observed using a scanning electron microscope (Carl Zeiss GmbH, Germany, model: Merlin) with an accelerating voltage of 15kV.

[0113] Vertical burning test: The vertical burning test was conducted according to ASTM D6413 standard. The flame length of the alcohol lamp was 40 mm, the distance from the bottom of the sample to the wick was 20 mm, and the alcohol lamp was removed after burning for 20 seconds. The burning phenomenon was recorded.

[0114] Limiting oxygen index: In accordance with ASTM D2863-2009 standard, an oxygen index tester (Nanjing Jiangning Analytical Instrument Co., Ltd., model: JF-3) was used to test a silicone foam material sample with a size of 100mm×10mm×10mm.

[0115] X-ray diffraction analysis (XRD): The residue after sample burning was measured and its diffraction information was collected using an X-ray diffractometer (Panaco, Netherlands, model: X Pert Pro). The test tube voltage was 40 kV, the tube current was 40 mA, the scanning rate was 2° / min, and the scanning angle was 5° to 80°.

[0116] Fire warning test: Connect a sample of appropriate size to a digital multimeter (Keithley, USA, model: DMM65006 1 / 2) and a millivolt voltage alarm. Burn the sample with the outer flame of an alcohol lamp. For thermal resistance warning, the warning resistance change rate is 90%. For thermoelectric warning, the warning voltage is 1mV. Record the warning response time of the sample.

[0117] Human motion detection: The sample was connected to the human joint and a digital multimeter (Keithley, USA, model: DMM6500 6 1 / 2) using copper wires, and the resistance change curve was recorded.

[0118] Thermal insulation performance test: The sample was fixed 10cm away from the butane spray gun nozzle and close to the infrared thermal imager (Shanghai Thermal Imaging Technology Co., Ltd., model: Fotric 226s). The infrared thermal imager was used to record the temperature distribution image on the back of the sample. The sample size was 80mm×80mm×15mm.

[0119] Conductivity test: The resistance of the sample was tested using a four-probe resistance meter (Guangzhou Four-Probe Technology Co., Ltd., RTS-9).

[0120] Specific tests:

[0121] 1) The cell growth process diagram of the fire-retardant and conductive silicone foam material in Example 1 is shown below. Figure 1 As shown.

[0122] Depend on Figure 1 It can be seen that the foaming process begins with the hydrogen evolution reaction between H2O and the hydroxyl groups of titanium carbide and hydrogen-containing silicone oil. Bubbles gradually form and grow as hydrogen is released, subsequently merging with adjacent bubbles to form larger bubbles, approximately 200 μm in diameter. The entire process, from the initial bubble growth to merging into a 200 μm diameter bubble, takes only about 40 seconds. At room temperature, the foaming process can be completed in just a few minutes, demonstrating that the foaming process of the fire-retardant conductive silicone foam material of this invention is very rapid and possesses the characteristics of simplicity, environmental friendliness, and high efficiency. Furthermore, the fire-retardant conductive silicone foam materials of Examples 2-8 can also achieve the same room-temperature foaming process.

[0123] 2) SEM images and elemental distribution diagrams of the cross-section of the fire-retardant and conductive silicone foam material in Example 1 are shown below. Figure 2 As shown.

[0124] Depend on Figure 2 It can be seen that the inner walls of the foam cells mostly exhibit a wrinkled morphology, and the elemental distribution map shows that the Si content decreases and the Ti content increases compared with the cross-sectional skeleton, indicating that titanium carbide is assembled on the inner walls of the foam cells. In addition, the same test found that the nano-conductive filler in the fire-retardant conductive silicone foam materials of Examples 2-8 also achieved assembly on the inner walls of the foam cells.

[0125] 3) The mechanical property test results of the fire-retardant and conductive silicone foam material in Example 1 are shown in the figure below. Figure 3 As shown.

[0126] Depend on Figure 3 It can be seen that the fire-retardant conductive silicone foam material of Example 1 has good flexibility and stretchability, and will not break even when bent 180° and stretched by 60%. In addition, the same tests showed that the fire-retardant conductive silicone foam materials of Examples 2 to 8 also have excellent mechanical properties.

[0127] 4) High-temperature insulation tests were conducted on the silicone foam material of Comparative Example 1 and the fire-retardant conductive silicone foam material of Example 1 (Test procedure: A butane spray gun with a flame temperature of approximately 1200℃ was used to burn the surface of a sample measuring 8cm × 8cm × 1.5cm, with a distance of 10cm between the spray gun nozzle and the sample surface, for 300s). The resulting images are shown below. Figure 4 and Figure 5As shown, the X-ray diffraction (XRD) pattern of the ceramic-like body (intermediate layer) formed after high-temperature thermal insulation testing of the fire-resistant conductive silicone foam material of Example 1 is as follows. Figure 6 As shown.

[0128] Depend on Figures 4-6 It can be seen that the silicone foam material of Comparative Example 1 completely lost its heat insulation performance after being burned, and the resulting residue was fluffy and brittle. However, the fireproof and conductive silicone foam material of Example 1 maintained its structural integrity after being burned. When the cross-section was observed after being cut along the center line, it was found that only white silica existed on the surface of the sample. A little deeper into the surface, a relatively hard and dense black ceramic-like body was distributed in an arc shape. Diffraction peaks belonging to quartz, cristobalite and rutile appeared in the middle layer of the ceramic-like body, indicating that a ceramic layer was formed in the middle layer of the sample and a new crystal phase appeared.

[0129] 5) Conductivity tests, limiting oxygen index tests, vertical burning tests, repeated fire early warning tests, and repeated piezoresistive sensing tests were conducted on the fire-resistant conductive silicone foam materials of Examples 1-8 and the silicone foam materials of Comparative Examples 1-3. The test results are as follows:

[0130] a) Screenshot of the fire warning test video of the fire-resistant conductive silicone foam material in Example 1, as shown below. Figure 7 As shown;

[0131] b) The repeated piezoresistive sensing test results of the fire-retardant conductive silicone foam material in Example 1 are shown in the figure below. Figure 8 As shown;

[0132] c) The electrical conductivity and density of the fire-resistant conductive silicone foam materials of Examples 1-8 and the silicone foam materials of Comparative Examples 1-3 are shown in Table 1. The results of oxygen index, vertical burning test, and repeated fire warning test are shown in Table 2.

[0133] Table 1 Conductivity and Density

[0134]

[0135] Table 2 Results of Oxygen Index, Vertical Combustion Test, and Repeat Fire Warning Test

[0136]

[0137] Table 1 shows that the fire-retardant and conductive silicone foam materials in Examples 1-8 all have good conductivity, while the silicone foam materials in Comparative Examples 1-3 are all non-conductive. The density of the fire-retardant and conductive silicone foam materials in Examples 1-8 is 360 mg / cm³. 3 ~560mg / cm 3 Within a certain range, it has low density and is lightweight.

[0138] Depend on Figure 7As shown in Table 2, when the fire-resistant conductive silicone foam material of Example 1 is ignited by a flame, due to the thermoelectric effect of multi-walled carbon nanotubes and titanium carbide, the internal charge carriers move along the temperature gradient, outputting a voltage. When the preset trigger value is reached, the warning device is triggered. The warning device is triggered in only 2.4 seconds on the first ignition. Furthermore, thanks to the thermoelectric reversibility, repeated warnings can be achieved. After 30 repeated warning tests, the warning device can still be triggered in 4.1 seconds. This indicates that the fire-resistant conductive silicone foam material of the present invention has a sensitive and repeatable fire warning capability, which can not only greatly improve the fire safety of silicone foam materials, but also avoid the hazards caused by fire reignition.

[0139] Depend on Figure 8 It can be seen that, thanks to its porous structure and good conductivity, the fire-resistant conductive silicone foam material of Example 1 can be used for piezoresistive sensing tests. In the resistance change curve after 500 compression cycles, it can be seen that the curve does not change much, indicating that it has excellent repeatable piezoresistive sensing performance and durability.

[0140] Table 2 shows that the fire-retardant and conductive silicone foam materials in Examples 1-8 all exhibit excellent flame-retardant and fire warning performance. The silicone foam material without nitrogen-containing silanes, carbon nanotubes, and assembled nano-conductive fillers (Comparative Example 1) has a low oxygen index and burns completely in the vertical combustion test, thus failing to provide a fire warning function. The addition of nitrogen-containing silanes (Comparative Example 2) improves the flame-retardant performance and oxygen index, enabling self-extinguishing within 20 seconds, but it still lacks conductivity and therefore does not provide fire warning performance. The silicone foam material assembled with nano-conductive fillers (Comparative Example 3) further improves the oxygen index and self-extinguishes within 13 seconds; however, due to the incomplete construction of the conductive network, it still cannot conduct electricity. Electricity does not provide fire warning capabilities. However, after introducing carbon nanotubes and nano-conductive fillers to synergistically construct a conductive network (Examples 1-8), the silicone foam material exhibits excellent flame retardant properties. The flame can be extinguished rapidly within 10 seconds after leaving the fire source. This is mainly because at high temperatures, the nitrogen-containing silanes in the silicone matrix coordinate with platinum, inhibiting the aggregation of platinum atoms under high temperature. This facilitates the efficient catalysis of free radical cross-linking reactions of the silicone matrix by platinum atoms at high temperatures. Meanwhile, the one-dimensional / two-dimensional nanomaterial network can act as a skeletal support, synergistically forming a more solid and dense ceramic barrier layer, which acts as a barrier against heat and oxygen, thereby endowing the silicone foam material with excellent flame retardant and high-temperature insulation properties.

[0141] In summary, the fire-retardant conductive silicone foam material of the present invention has excellent electrical conductivity, high-temperature insulation, flame retardancy, fire early warning and piezoresistive sensing properties. In addition, thanks to its good electrical conductivity and the interface assembly of nano-conductive fillers, it also has electromagnetic shielding properties and can be applied in aerospace, intelligent fire protection, electronic communication and national defense industries.

[0142] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A fire-retardant and conductive silicone foam material, characterized in that, The components include the following parts by weight: Vinyl silicone oil: 100 parts; Hydrogen-containing silicone oil: 30 to 60 parts; Nano-conductive filler: 0.3 parts to 10 parts; Nitrogen-containing silane-modified carbon nanotubes: 0.5 parts to 15 parts; Organoplasmium compounds: 0.2 to 1.5 parts; Inhibitor: 0.02 to 0.5 parts; The nano-conductive filler is at least one of graphene oxide, aminated graphene oxide, carboxylated graphene oxide, titanium carbide, molybdenum carbide, and titanium nitride. The nitrogen-containing silane in the nitrogen-containing silane-modified carbon nanotubes is γ-silane. aminopropyltrimethoxysilane, γ Piperazinylpropylmethyldimethoxysilane, N (β Aminoethyl γ At least one of (aminopropyl)methyldimethoxysilane; The fire-retardant and conductive silicone foam material is prepared by a method including the following steps: 1) Mixing vinyl silicone oil, an ethanol dispersion of nitrogen-containing silane-modified carbon nanotubes and an organoplasmic compound to form mixture A, and mixing hydrogen-containing silicone oil, an aqueous dispersion of nano-conductive fillers and an inhibitor to form mixture B; 2) After mixing mixture A and mixture B, injecting the mixture into a mold, then performing cross-linking-foaming at room temperature, and then performing cross-linking curing after heating to obtain the fire-retardant and conductive silicone foam material.

2. The fire-retardant and conductive silicone foam material according to claim 1, characterized in that: The viscosity of the vinyl silicone oil is 5000 mPa·s to 60000 mPa·s.

3. The fire-retardant and conductive silicone foam material according to claim 1, characterized in that: The hydrogen content of the hydrogen-containing silicone oil is 0.5wt% to 1.4wt%.

4. The fire-retardant and conductive silicone foam material according to any one of claims 1 to 3, characterized in that: The mass ratio of nitrogen-containing silane to carbon nanotubes in the nitrogen-containing silane-modified carbon nanotubes is 0.1 to 1.5:

1.

5. The fire-retardant and conductive silicone foam material according to any one of claims 1 to 3, characterized in that: The carbon nanotubes in the nitrogen-containing silane-modified carbon nanotubes are at least one of carbon nanotubes, carboxylated carbon nanotubes, aminated carbon nanotubes, and hydroxylated carbon nanotubes.

6. The fire-retardant and conductive silicone foam material according to any one of claims 1 to 3, characterized in that: The nitrogen-containing silane-modified carbon nanotubes have a length of 20 μm to 100 μm and an outer diameter of 10 nm to 20 nm.

7. The fire-retardant and conductive silicone foam material according to any one of claims 1 to 3, characterized in that: The organoplatinum compound is at least one of methylvinylsiloxane-platinum complex and vinylpolysiloxane-platinum complex; the inhibitor is 2-methyl-3-butyn-2-ol, 1 Acetylene 1 At least one of cyclohexanol.

8. The fire-retardant conductive silicone foam material as described in any one of claims 1 to 7 is used for flame retardant insulation, fire early warning, piezoresistive sensing, or electromagnetic shielding.

Citation Information

Patent Citations

  • Conductive particle / silicone rubber pressure-sensitive material as well as preparation method and application thereof

    CN103525093A

  • Tear-resistant organosilicon foamed material and preparation method thereof

    CN110894363A

  • Improved conductive rubber composition and preparation method thereof

    CN112409657A